Perceived Self-Efficacy of Pre-Service Agricultural Science Teachers toward Agricultural Mechanization - Hainline, Mark S.; Sorensen, Tyson J.; Chumbley, Steven (Journal of Agricultural Systems, Technology, and Management, 2018)
This study explored the perceived self-efficacy towards teaching agricultural mechanics of pre-service agriculture teachers in Texas. Two students from Texas Tech University were purposefully selected to participate based on their completion of agricultural mechanics coursework. Interviews were conducted and data were collected and coded from the transcribed transcripts. Four major themes, with six sub-themes emerged from the data: a) mastery learning and teaching experiences (i.e., experiences with technical agricultural mechanics content; and mastery teaching experiences); b) emotional arousal (i.e., fear and anxiety; and enthusiasm); c) content knowledge (i.e., lack of knowledge, experiences, and opportunities to learn; and confidence in the basics but apprehension towards subject complexity); and d) social persuasion. Overall, the participants felt confident in their ability to teach basic concepts within agricultural mechanics but expressed fear and anxiety to teach more complex topics and to manage the shop and safety. Much of the fear and anxiety was a product of the participants’ lack of experiences with the technical content of agricultural mechanics. Recommendations for practice and research are shared.